2017
DOI: 10.1002/jsid.527
|View full text |Cite
|
Sign up to set email alerts
|

Monocular hyper‐realistic AR head‐up display

Abstract: -We proposed and developed a novel monocular hyper-realistic head dome projector for an amusement application and a novel monocular windshield augmented reality projector for augmented reality and head-up display applications. They use monocular vision that eliminates the depth cues caused by binocular parallax information. Our developed monocular hyper-realistic head dome projector and windshield augmented reality projector system achieved a high hyper-reality performance with free depth perception and high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Head Dome Projector (HDP) was a primitive experimental system reflecting our considerations. Simple projection of conventional images on a spherical dome screen, which was only 40 cm in diameter, realized a hyper‐realistic immersive display system …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head Dome Projector (HDP) was a primitive experimental system reflecting our considerations. Simple projection of conventional images on a spherical dome screen, which was only 40 cm in diameter, realized a hyper‐realistic immersive display system …”
Section: Introductionmentioning
confidence: 99%
“…Simple projection of conventional images on a spherical dome screen, which was only 40 cm in diameter, realized a hyperrealistic immersive display system. 3 In the field of medical equipment, the innovation of medical technology progressed. Moreover, the importance of patient care during medical examination was increasingly recognized.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the development of the research on the hyperrealistic display was advanced. It was found that when a user faces the non-plane display of a wide visual field, monocular vision affects the reinforcement of the space perception and stereoscopic sense [10]. Based on these results, depth perception enhancement through monocular vision was used for the development of a new-concept HUD.…”
Section: Introductionmentioning
confidence: 99%
“…We thus find that monocular vision affects the reinforcement of space perception and that the reinforcement of the stereoscopic sense is 0.5-1.3 points higher than for binocular vision (see Figure 1). 3,4 We have therefore used these depth perception monocular vision enhancement results to develop a new monocular HUD concept, which we call the windshieldrefracted augmented reality projector (WARP). In this system (see Figure 2), the display image can be set to any depth position and thus represents an improvement over conventional approaches.…”
mentioning
confidence: 99%